Integration of DERs for Optimal Sharing of Power in Grid Connected Mode as Well as Islanded Mode - Bangar Raju, L; Subba Rao, K (International Journal of Engineering and Technology, 2018)
The Microgrid consists of distributed energy resources, DERs(distributed generators - DGs) and distributed storages - DSs), loads, PCC, energy management controllers etc., which are required for effective, efficient, reliable and seamless operation of microgrid in both grid connected mode and islanded mode. The heart of the microgrid is the integration part of the DERs with energy management controllers. Out of the methods available, hierarchical method of integrating DERs is selected in this paper. The method is based on the principle of hybrid particle swarm optimization (PSO) which takes into account of genetic algorithm (GA) and PSO. In this paper, the best part of particle to particle information sharing in GA is combined with fast convergence option in PSO, to get the optimum solution with minimum no of iterations. Integration of DERs is nothing but energy management in supply side management (SSM) as well as demand side management (DSM). DSM consists of load shedding or load shifting to an alternate feeder. The primary energy controller MC (microsource controller) controls voltage and frequency through droop control inverters. The secondary controller (MGCC) monitors the flow of active and reactive power in the microgrid and communicates to the DMS (distribution management system). The tertiary controller, DMS takes care of overall control of the network like export, import, islanding, economical aspects of the DERs operation in the microgrid. The energy management module (MGCC) must also contain protection co-ordination module (PCM) along with energy management module (EMM), for relay co-ordination as microgrid consists of two operating modes viz., grid connected mode and islanded mode. The fault currents substantially reduces to smaller values in islanded mode as DERs inertias are low. For this reason the PCM must have two settings and auto changeover of settings are required from one mode to another by PCM module to suit islanding and grid modes.Â Â Â